Business Networks and Cooperation in International Business Relationships - Holm, Desirée Blankenburg; Eriksson, Kent; Johanson, Jan (Journal of International Business Studies, 1996)
Cooperative relationships between firms can be better understood if they are examined in the context of a network of connected business relationships. Based on research on business relationships and business networks, this paper formulates a LISREL model that analyses cooperation in international business relationships between suppliers and customer firms. Theory suggests that cooperation can raise the value of business relationships, and that business network connections have an impact on cooperation. The model is investigated in a sample of 136 international business relationships. The analysis shows that relationship profitability is directly affected by relationship commitment and, indirectly through commitment, by business network connections.